Students with autism in the regular classroom: what to do? (Research, Society and Development, 2016)
The students are part of the important world of school space actors. Right space, regardless of the actions to learn, teach, share knowledge, information. The aim of this paper is to discuss a student with Autistic Disorder Spectrum-TEA, enrolled in public school. We believe in learning ability through dedication, effort; but also, when motivated, encouraged, supported. We investigate their academic needs through observation and review the literature on the possible resources to be used. Evidence shows the importance of family involvement in children's development, sensitivity to observe behavioral minutiae, interactions with peers, giving meaning to their experiences through inclusive education. On the one hand, the school has articulated its specific actions; the other, the family has disowned the guidelines, forgetting the students needs and legislation recommendations with regard to family duty.